Evaluation Study of Traditional Chinese Medicine Syndrome Differentiation Therapy on the Quality of Life and Efficacy Satisfaction in Elderly Community-acquired Pneumonia Patients after Discharge - WANG Minghang, HAN Weihong, BI Lichan, YANG Jiang, LI Jiansheng (Zhongguo quanke yixue, 2024)
Background Community-acquired pneumonia (CAP) is one of the common infectious diseases, especially in elderly patients, with atypical clinical symptoms, which is susceptibility to serious complications, lacks effective treatment measures, and often has a poor prognosis. Objective To investigate the effect of traditional Chinese medicine (TCM) syndrome differentiation therapy on the quality of life and efficacy satisfaction of elderly patients with CAP discharged from hospital (within 1 week) . Methods This study was designed as a multicentre, randomized double-blind placebo clinical study. Elderly CAP post-discharge patients admitted to the respiratory departments of the First Affiliated Hospital of Henan University of Traditional Chinese Medicine, Henan Chest Hospital, Henan People's Hospital, Zhengzhou Hospital of Traditional Chinese Medicine and Zhengzhou People's Hospital from April 2018 to January 2020 were selected as the study subjects and divided into the experimental group and control group by using a central randomized group enrolment model. The patients in the experimental group were treated with corresponding TCM granules based on syndrome differentiation, and the lung-tonifying spleen-invigorating phlegm-reducing formula was given for syndrome of phlegm-dampness due to qi deficiency, and the qi-supplementing yin-nourishing lung-clearing formula was given for qi and yin deficiency and phlegm-heat syndrome. The control group was given a placebo with the same appearance, weight, color, and smell as the Chinese medicine granules. The treatment course was 2 months, and the follow-up was up to 6 months. The quality of life evaluated by the Chinese version of the Quality of Life Rating Scale (SF-36) and efficacy satisfaction evaluated by the Efficacy Satisfaction Questionnaire for CAP (ESQ-CAP) were compared between the two groups before the treatment, 1 month after the treatment, 2 months after the treatment, 3 months after the follow-up, and 6 months after the follow-up. Results Among the 120 subjects included, 8 were dislodged and 112 were finally included that met the protocol set, including 54 cases in the experimental group and 58 cases in the control group. There was no significant difference in gender, age, time after discharge, TCM syndrome differentiation, CUBR-65 score, and underlying diseases between the two groups before treatment (P>0.05) . The main effects of the group were significant on SF-36 physiological function domain score (Fgroup=5.057, Pgroup=0.027) , general health domain score (Fgroup=7.286, Pgroup=0.008) , and role limitations due to emotional problems domain score (Fgroup=6.858, Pgroup=0.010) . Comparison between the two groups showed that SF-36 physical function domain score of the experimental group was higher than that of the control group at 2 months of treatment, 3 months of follow-up, and 6 months of follow-up (P<0.05) ; SF-36 general health status domain and role limitations due to emotional problems domain scores of the experimental group were higher than those of the control group at 1 and 2 months of treatment, 3 and 6 months of follow-up (P<0.05) ; the SF-36 domain score for role limitations due to mental health was higher than that of the control group (P<0.05) at 3 and 6 months of follow-up. The main effect of group on ESQ-CAP daily living and ability domain score (Fgroup=16.218, Pgroup<0.001) , convenience domain score (Fgroup=25.013, Pgroup<0.001) , and ESQ-CAP total score (Fgroup=13.843, Pgroup<0.001) was significant. The ESQ-CAP daily living and ability domain scores were higher in the experimental group than the control group at 2 months of treatment, 3 and 6 months of follow-up (P<0.05) . At 1 and 2 months of treatment and 3 and 6 months of follow-up, ESQ-CAP convenience domain score and ESQ-CAP total score were higher in the experimental group than in the control group (P<0.05) . At 3 months of follow-up, the ESQ-CAP overall efficacy domain score was higher in the experimental group than the control group (P<0.05) . Conclusion The TCM syndrome differentiation therapy scheme can improve the quality of life and efficacy satisfaction of elderly patients with CAP after discharge.